Clinical epidemiological characteristics of mycetoma in Eastern Sennar locality, Sennar State, Sudan - Hassan, Rowa; Deribe, Kebede; Fahal, Ahmed Hassan; Newport, Melanie; Bakhiet, Sahar (PLOS Neglected Tropical Diseases, 2021)
Author summary Mycetoma is a neglected tropical disease documented in many countries around the world, yet few community-based studies have been performed investigating the disease burden, clinical epidemiological features, and risk factors. The overall prevalence of mycetoma in the study area was 0.87%, and the prevalence of mycetoma among males and females was almost the same. Individuals in the age group 31–54 years had the highest prevalence among all age groups. Married individuals had a higher prevalence when compared to unmarried individuals. Prevalence among those who could not read or write was 1.24% compared to 0.87% in those who could. History of trauma increased the prevalence to 1.63%, while individuals with no history of trauma had a prevalence of 0.70%. There were nine villages with no cases and an average of seven cases per village across the other 51 villages (range 1–39). The prevalence map showed patients clustered within the central and north-eastern part of the locality, while villages in the south-western part had few or no cases. The disease prevalence reported here may be more accurate as it was generated from a large study population. Further epidemiological studies are needed to determine mycetoma prevalence in Sudan and bridge the gaps in our understanding of the epidemiology of mycetoma.